Effects of tropical montane forest disturbance on epiphytic macrolichens - Benitez Chavez, A. (2017)
The high diversity of epiphytes typical of undisturbed montane tropical forests has been negatively affected by continuous deforestation and forest conversion to secondary vegetation. Macrolichens are an important component of these epiphytes. Because their physiology is strongly coupled to humidity and solar radiation, we hypothesized that microclimatic changes derived from forest clearing and logging can affect the diversity of these poikilohydric organisms. In southern Ecuador, we examined three types of forests according to a disturbance gradient (primary forests, secondary forests, and monospecific forests of Alnus acuminata) for the presence/absence and coverage of epiphytic macrolichens that we identified on 240 trees. We found that total richness tended to decrease when the range of the disturbance increased. The impoverishment was particularly drastic for shade-adapted lichens , while the richness of heliophytic lichens increased in the drier conditions of secondary growth. Epiphytic composition also differed significantly among the three types of forests, and the similarity decreased when the range of the disturbance was greater. We concluded that a span of 40. years of recovery by secondary vegetation was not enough to regenerate the diversity of epiphytic macrolichens that was lost due to forest disturbances. © 2012 Elsevier B.V.